On good form? Analysis of rail Signal Passed at Danger pro formas and the extent to which they capture systems influences following incidents. (July 2022) - Naweed, Anjum; Bowditch, Lorelle; Chapman, Janine; Dorrian, Jillian; Balfe, Nora
Highlights: Application of systems thinking in pro forma design and incident data capture. SPADs are currently being investigated using shallow methods of analysis. SPAD pro formas emphasise individual-level causation in findings and conclusions. A poorly designed pro forma may represent a contributory factor to SPAD incidents. First comprehensive hierarchical description of rail SPAD pro formas. Abstract: Through systems thinking it is recognised that human error is not a matter of personal control, but an emergent property of overall system design. In the context of rail, Signal Passed at Danger (SPAD) incidents are a weak link in an otherwise safe system and one of the few points where a single failure can have catastrophic consequences. One area overlooked in SPAD research is the investigation process itself, specifically in terms of what investigators do and do not look at when investigating incidents. The aim of this study was to examine the document (i.e. pro forma) investigators use to capture information and attribute SPAD causation, in order to determine the extent which systems thinking is reflected in the information captured. A qualitative cross-sectional multiple-case design was used to categorise a large dataset comprising completed SPAD pro formas ( n  = 208) from 10 rail organisations across Australasia. Conventional content analysis identified two types of SPAD pro forma (modulated, narrative) varying in length (long, short), and a comprehensive hierarchical description revealed shallow methods of analysis, and the tendency to emphasise and attribute SPAD causation to the individual-level (human error, personal factors) without identification of deeper underlying factors and other system influences. Findings are discussed in relation to the idea that SPAD pro formas are educative tools shaping the focus of investigations, and the observed deficiencies limit the learning that can be drawn from incidents and real change that can be achieved. SPAD pro forma development is needed, scaffolded by further research.